Fluorescent protein-based tumor models - Yagublu, Vugar; Ahmadova, Zhala; Hafner, Mathias; Keese, Michael (In vivo, 2012)
Numerous animal models have been developed to provide a deeper insight to tumor progression in the search for new therapeutic leverage. The closer the tumor model represents the real tumor disease, the better. The ideal model provides monitoring, tumor cell detection and quantification, and the physiological events involved in tumor progression and tumor dissemination, simultaneously. Sensitive techniques have been developed which involve fluorescent protein-based methods, developed in order to quantify the tumor cells in a whole organ, and in parallel, to visualize the cells. These genetically encoded fluorescent proteins may also be used to develop biological sensors to monitor the physiological reaction of tumor cells within whole organs in living animals. Here, we aim to review past and present work and to show the perspectives of animal models involving fluorescent protein-transfected tumor cells.